Optimization and Analysis of a High Power Density and Fault Tolerant Starter–Generator for Aircraft Application - Bo Wang; Gaurang Vakil; Ye Liu; Tao Yang; Zhuoran Zhang; Chris Gerada (Energies, 2020)
Permanent magnet synchronous machines provide many dramatic electromagnetic performances such as high efficiency and high power density, which make them more competitive in aircraft electrification, whereas, designing a permanent magnet starter–generator (PMSG), with given consideration to fault tolerance (FT), is a significant challenge and requires great effort. In this paper, a comprehensive FT PMSG design process is proposed which is applied to power systems of turboprops. Firstly, potential slot/pole combinations were selected based on winding factor, harmonic losses and manufacture issues. Then, pursuing high power density, a multiple objective optimization process was carried out to comprehensively rank performances. To meet a fault tolerance target, electrical, magnetic and thermal isolation topologies were investigated and compared, among which 18 slot/12 pole with dual three-phase was selected as the optimal one, with a power density of 7.9 kW/kg. Finally, a finite element analysis verified the performance in normal and post-fault scenarios. The candidate machine has merits concerning high power density and post-fault performance.